Somato-Regulatory Imbalance as a Pathophysiological Basis of Civilization Diseases - Gozhenko, Anatoliy; Gozhenko, Olena; Zukow, Walery; Pavlega, Hanna (Journal of Education, Health and Sport, 2025)
Background The global burden of non-communicable diseases (NCDs), particularly cardiovascular diseases (CVD) and type 2 diabetes mellitus (T2DM), continues to rise, posing a serious challenge to public health. Understanding the complex pathophysiological mechanisms underlying these conditions is critical for developing effective prevention and treatment strategies. Aim This study aims to investigate the interconnected pathways linking metabolic dysfunction, endothelial dysfunction, and cardiovascular complications, with a particular emphasis on the role of advanced glycation end-products (AGEs), reactive oxygen species (ROS), and dysregulation of the autonomic nervous system (ANS). Methods A comprehensive analysis of the renin-angiotensin-aldosterone system (RAAS), activation of the sympathetic nervous system (SNS), and dysfunction of endothelial nitric oxide synthase (eNOS) was conducted. Biomarkers were evaluated, including free fatty acids (FFAs), lipoproteins (HDL, LDL, VLDL), and inflammatory mediators such as interleukin (IL) and tumor necrosis factor alpha (TNF-α). Results The results demonstrate significant correlations between metabolic syndrome (MetS), endothelial dysfunction (ED), and ischemic heart disease (IHD). Elevated body mass index (BMI) and blood pressure (BP) were associated with increased somatoregulatory imbalance (SRI) and activation of the hypothalamic-pituitary-adrenal axis (HPA). Angiotensin-converting enzyme (ACE) activity showed strong associations with nitric oxide (NO) bioavailability and vascular function. Conclusions The study reveals complex interactions between metabolic and cardiovascular pathways, highlighting the importance of integrated therapeutic approaches targeting multiple systems simultaneously. These findings contribute to the understanding of the disability-adjusted life years (DALYs) burden and inform World Health Organization (WHO) guidelines on NCD prevention.